2018
DOI: 10.1016/j.midw.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mapping midwifery and obstetric units in England

Abstract: Both the availability and utilisation of midwifery units in England could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 19 publications
0
65
0
Order By: Relevance
“…However, there was little evidence of plans to scale up provision of midwife-led care across the system and to cater for a larger proportion of women who are considered low-risk. Sandall et al's study of maternity workforce indicated that around 45% of women would be eligible to plan labour in a midwife-led setting (Sandall, Murrells et al 2014), yet in the services we studied, only 10-14% of women were accessing midwifery unit care and nationally, the proportion remains similar (Walsh et al 2018). This may be a reflection of the perceptions expressed by many of our respondents, across all four sites, that despite expressions of support and national policy directives, the AMU continued to be regarded as marginal and additional to the OU, rather than as a core service.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, there was little evidence of plans to scale up provision of midwife-led care across the system and to cater for a larger proportion of women who are considered low-risk. Sandall et al's study of maternity workforce indicated that around 45% of women would be eligible to plan labour in a midwife-led setting (Sandall, Murrells et al 2014), yet in the services we studied, only 10-14% of women were accessing midwifery unit care and nationally, the proportion remains similar (Walsh et al 2018). This may be a reflection of the perceptions expressed by many of our respondents, across all four sites, that despite expressions of support and national policy directives, the AMU continued to be regarded as marginal and additional to the OU, rather than as a core service.…”
Section: Discussionmentioning
confidence: 71%
“…At the time of the data collection, professionals had access to the evidence from the Birthplace in England programme, but NICE guideline update was still in process. Nonetheless, recent mapping work indicates that change in practice has been limited, and confirms that managers continue to face challenges in providing, sustaining and scaling-up of midwifery units in England (Walsh et al 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Follow-on research projects from the Birthplace in England study 3 add that AMUs should be able to accurately identify their admissions and births in their record systems. 87 However, these criteria allow for a number of hybrid arrangements, for example: l midwifery-led rooms within the physical space of a traditional labour ward l a midwifery-led area adjacent to a labour ward, but with no separate staffing or management l a midwifery-led area that allows for labour interventions, such as continuous fetal monitoring l a midwifery-led area that is regularly used for labour ward overflow l no separate data collections of processes or outcomes within the MU.…”
Section: Definition Of Alongside Midwifery Unitsmentioning
confidence: 99%
“…A transfer time in excess of 30 minutes was given as another rationale for closure, despite the fact that audits of transfers from FMUs suggest that more than half are non-urgent. 87 In addition, there was no evidence from the Birthplace in England study 3 of poorer neonatal or maternal outcomes from FMUs 132 that are rurally located, and birth outcomes in countries with very rural populations, including Scotland, 135 New Zealand, 51 Canada 38 and Australia, 24 indicate that careful risk assessment and judicious decision-making that anticipates complications can ameliorate this. 136 In fact, none of the FMU closures from the media analysis or the HoM interviews had been precipitated by clinical incidents.…”
Section: Risk and Safetymentioning
confidence: 99%